Board gender diversity and ESG disclosure: The moderating role of audit committee - Ma, Yiming; Ahmad, Muhammad Ishfaq; Torelli, Riccardo (Corporate social-responsibility and environmental management, 2024)
This study analyzed whether the audit committee moderates the relationship between gender diversity and environmental, social, and governance (ESG) disclosures among Chinese listed firms. Data on energy sector companies from 2012 to 2022 were taken from the Chinese Stock Market and Accounting Research database to test the moderation model. Gender diversity was measured as the percentage of females on boards using the Blau and Shannon indices. Board gender diversity directly and positively affected both the overall and individual dimensions of ESG disclosures. Furthermore, the audit committee moderated the relationship between gender diversity and ESG disclosure. This study provides valuable insights for managers and investors to evaluate the role of gender diversity and audit committees in ESG disclosures and facilitates them in making better decisions. Furthermore, regulators can revise corporate governance codes to promote more female inclusion not only on corporate boards but also on subcommittees to protect the rights of stakeholders.